2014
DOI: 10.1093/gbe/evu045
|View full text |Cite
|
Sign up to set email alerts
|

chlB Requirement for Chlorophyll Biosynthesis under Short Photoperiod in Marchantia polymorpha L.

Abstract: Chlorophylls (Chls) play pivotal roles in energy absorption and transduction and also in charge separation in reaction centers in all photosynthetic organisms. In Chl biosynthesis steps, only a step for the enzymatic reduction of protochlorophyllide (Pchlide) to chlorophyllide (Chlide) is mediated by both nuclear- and chloroplast-encoded genes in land plants. Many plants encode the genes for light-dependent Pchlide reductase (LPOR) and light-independent Pchlide reductase (DPOR) in the nucleus and chloroplast g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…More chlorophyll contents were accumulated in the ygl18 leaves when grown under a longer light application time (Figures 9A,B ). Similar phenomena were found from the chlB knockout mutant in liverwort ( Marchantia polymorpha L.), where it was suggested that chlB was required for chlorophyll biosynthesis under short photoperiod (Ueda et al, 2014 ). Nevertheless, there may be a different explanation for this phenomenon in ygl18 .…”
Section: Discussionsupporting
confidence: 65%
“…More chlorophyll contents were accumulated in the ygl18 leaves when grown under a longer light application time (Figures 9A,B ). Similar phenomena were found from the chlB knockout mutant in liverwort ( Marchantia polymorpha L.), where it was suggested that chlB was required for chlorophyll biosynthesis under short photoperiod (Ueda et al, 2014 ). Nevertheless, there may be a different explanation for this phenomenon in ygl18 .…”
Section: Discussionsupporting
confidence: 65%
“…Disruption of the ChlB gene from plastome of Chlamydomonas reinhardtii developed yellow mutants (Liu et al, 1993), whereas null mutants of cyanobacterium failed to synthesize chlorophyll under dark conditions . However, disruption of ChlB from liverwort Marchantia polymorpha L. resulted in low chlorophyll synthesis in dark and revealed the importance of ChlB, which is particularly required for protochlorophyllide reduction under short day conditions (Ueda et al, 2014). These research findings clearly suggest that the ChlB has a pivotal role in the activity of DPOR.…”
Section: Introductionmentioning
confidence: 78%
“…Known as the source of the first plastid DNA genome sequence to be reported ( Ohyama et al 1986 ), the chloroplast of Marchantia is an interesting platform for plastid gene expression studies due to its relationship to the earliest terrestrial plants ( Edwards et al 1995 , Wellman et al 2003 ). Aspects of evolutionary divergence between liverwort and angiosperm chloroplasts have been investigated in the context of RNA editing ( Ohyama et al 2009 ), photosynthesis-related enzymes ( Ueda et al 2012 , Ueda et al 2014 ) and sigma factors ( Ueda et al 2013 ). For a decade after the initial demonstration of transformation of chloroplasts in M. polymorpha by particle bombardment ( Chiyoda et al 2007 ), the aadA resistance marker remained the only heterologous gene to be successfully expressed in this organelle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, M. polymorpha is one of only a handful of plant species for which stable chloroplast transformation has been confirmed to date ( Bock 2015 ). Three studies have reported generation of stable transplastomic lines of M. polymorpha by particle bombardment of 5- to 7-day-old sporelings, followed by propagation under selective conditions for several months to establish homoplasmy ( Chiyoda et al 2007 , Ueda et al 2012 , Ueda et al 2014 ). However, all three studies were limited to employing an aadA expression cassette conferring resistance to the antibiotic spectinomycin as the sole marker ( Svab et al 1990 ).…”
Section: Introductionmentioning
confidence: 99%